Code blue - Michaels, Fern (Michaels, Fern. Sisterhood., 2025)
"Theresa Gallagher has never met her Aunt Dottie, though she remembers her mother's stories about the wild sister who left home at seventeen and moved out west. When a letter arrives from one of Dottie's neighbors, telling Theresa that her aunt is now incapacitated and in a nursing home, Theresa decides to fly out to Arizona to see her. After all, family is family. The staff at the Sunnydale Care Facility seem pleasant and efficient, but Theresa finds it strange that she's only permitted to 'observe' her elderly aunt from a viewing room. It's the first of several red flags that lead Theresa to start asking questions. Is it just coincidence that as soon as she does, her car is almost run off the road? Theresa contacts her attorney friend, Lizzie Fox, who just happens to be connected to a group of women uniquely posed to get answers. Soon the Sisterhood is on the case, uncovering evidence suggesting that behind Sunnydale's compassionate image hides a greedy, cruel enterprise. At Sunnydale centers all over the country, seniors are mistreated, duped, and drained of their savings. And with powerful political figures at the helm, staying one step ahead of legislation and investigation, it seems like the perfect scam. But no one is beyond justice--not when the Sisterhood's extraordinary women are involved, making wrongs right as only they can." -- Provided by publisher.